A Phenomenological Exploration of Academically Gifted Individuals Who Are Deaf or Hard of Hearing - Ophélie Allyssa Desmet; Sofia Ippolito; Jenna Herren; Sophia Guzman-Roman (Education Sciences)
Academically gifted individuals who are Deaf or hard of hearing (DHH) represent a unique intersection of identities that can significantly affect various aspects of their lives. This qualitative phenomenological study explored the lived experiences of academically gifted DHH individuals to gain insights into their unique challenges and strengths. Semi-structured interviews were conducted with 10 participants (ages 21–85) who self-identified as both academically gifted and DHH. Interpretative phenomenological analysis of the participants’ experiences revealed themes such as resilience, self-acceptance, family support, educational accommodations, and social challenges. The participants demonstrated remarkable adaptability in navigating both academic and social environments, often developing innovative coping strategies. These findings highlight the need for tailored educational approaches and support systems that recognize and nurture the potential of gifted DHH students.